All Quiet on the Protest Scene? Repertoires of Contention and Protest Actors During the Great Recession - Sophia Hunger; Jasmine Lorenzini (Contention in Times of Crisis. Recession and Political Protest in Thirty European Countries, 2020)
The choice of specific action repertoires allows protesters to increase their visibility and eventually their success. A rise in protest, i.e. a protest wave, often comes with a qualitative expansion of the conflict, which can take two forms: changes in the action repertoire and a growing diversity of involved actors. In this chapter, we examine the types of protest and the types of actors over time. In so doing, we ask whether and how the Great Recession transformed customary action repertoires in southern, north-western, and eastern Europe. Hence, we show variations in the use of commonplace action forms, i.e. demonstrations, strikes, and confrontational and violent actions. We find that demonstrations and strikes remain the dominant form of protest across regions and time periods, while transformations in the action repertoire of contention, in the form of violent events, took place only in some parts of the south and were short lived. Lastly, we turn to actors and we show that protest events increasingly feature social groups without formal organizational structures. We conclude by arguing that contention repertoires remained largely unaffected by the Great Recession; demonstrations were and remained the prevailing form of protest in all three regions during the whole period under study.
Keywords: 300; action repertoire; protest forms; protest actors; forms of contention; Great Recession